Rooting Responses of Hardwood Stem Cuttings of Juniper to Exogenous Hormone Treatment - Wani, M. A. (Indian Forester, 2018)
Vegetative propagation through stem cuttings of Juniperus communis was tested by treatments with different concentrations of root promoting hormones like Indole-3 acetic acid (IAA), Indol-3-butyric acid (IBA), Naphthalene acetic acid (NAA) and synergistic combinations of IBA & NAA in the range of 0.2M to 1M concentrations respectively. The trials were conducted under both greenhouse and open nursery conditions. Data collected on percentage rooting, average root length, average root number, bud sprouting and survival rate were subjected to Analysis of Variance (ANOVA) to determine the level of significance. The highest rooting rate (80 per cent) was recorded in the cuttings treated with 0.8M concentrations of IBA as compared with that of control which was recorded as only 20 per cent. Other treatments of IAA, NAA, IBA and synergistic combinations of IBA+NAA also exhibited improved response over the control, both under greenhouse and open conditions. It was concluded that IAA and IBA was a better applied concentration for rooting in Juniperus cuttings.